ANALISI PENGARUH DEWAN PENGAWAS SYARIAH DAN INTELLECTUAL CAPITAL TERHADAP CORPORATE SOCIAL RESPONSIBILITY PADA BANK SYARIAH DI INDONESIA - Rahmah Aulia Haryani; Aditya Septiani (Diponegoro Journal of Accounting, 2015)
The purpose of this study is to observe the influence of the presence of sharia supervisory board (DPS) and intellectual capital towards corporate social responsibility practices (CSR). Intellectual capital consists of three elements which are Human Capital Efficiency (HCE), Structural Capital Efficiency (SCE), and Capital Employed Efficiency (CEE). The method which is being used by this study is secondary data analysis towards annual reports of sharia bank published in Indonesia. It is using purposive sampling method. This study uses multiple regression analysis. The data includes 11 banks in Indonesia for 2011 – 2013. This study found that the presence of sharia supervisory board has influence towards the report of corporate social responsibility. Intellectual capital which consists of HCE, SCE and CEE has difference influence. HCE and SCE have no significant influence but CEE has positive influence towards corporate social responsibility.